Study of the negative magneto-resistance of single proton-implanted lithium-doped ZnO microwires - Lorite, I. (2015)
The magneto-transport properties of single proton-implanted ZnO and of Li(7%)-doped ZnO microwires have been studied. The as-grown microwires were highly insulating and not magnetic. After proton implantation the Li(7%) doped ZnO microwires showed a non-monotonous behavior of the negative magneto-resistance (MR) at temperature above 150 K. This is in contrast to the monotonous NMR observed below 50 K for proton-implanted ZnO. The observed difference in the transport properties of the wires is related to the amount of stable Zn vacancies created at the near surface region by the proton implantation and Li doping. The magnetic field dependence of the resistance might be explained by the formation of a magnetic/non-magnetic heterostructure in the wire after proton implantation.